On the leaching of mercury by brackish seawater from permeable barriers materials and soil. Issue 2 (June 2015) - Kozyatnyk, Ivan; Lövgren, Lars; Haglund, Peter
Highlights: Hg ions are associated with the high molecular weight fraction of DOM. Fly ash has high potential to remove mercury and DOM from groundwater. Artificial brackish seawater do not elute mercury from studied materials. There is low risk that brackish seawater mobilizes mercury from soil and barriers. Abstract: Soils at former pulp, paper and chemical plants in the subarctic (boreal) zone, including Canada, Scandinavia, Russia, and parts of the USA, are often contaminated with organic pollutants and heavy metals, of which mercury is one. The soil- and ground-water at these sites is often rich in dissolved organic matter (DOM), particularly fulvic substances. Permeable barriers are sometimes used to limit the migration of pollutants with groundwater and protect nearby aquatic environments. These are installed downstream of the source, generally close to the receiving water body. In cases when such barriers have been installed close to the sea, concerns have been raised that the seawater may back-flush the barrier and release mercury, often a key contaminant, in the form of stable chloride complexes. Intrusion of seawater into coastal groundwater reservoirs has previously been shown to result in dissolution of mercury from soil. Less is known about the ability of brackish water, present in estuaries or brackish seas, to mobilize mercury from soil or from barrier materials. We therefore investigated the effect of artificial brackish seawater (6.3‰ salinity) on the sorption and desorption of mercury from different barrier materials (activated carbon, fly ash, lignite, torrified material, peat, and iron powder). The mercury was found to be associated with the high molecular weight fraction of groundwater DOM and it was concluded that the mercury was removed (sorbed) as relatively strong DOM-complexes. Chloride ions did not seem to form aqueous complexes with mercury to any great extent and artificial brackish seawater did not desorb mercury from the contaminated soil or from the studied barrier materials.